SAT0687 EVOLVING THE MANAGEMENT OF RHEUMATOID ARTHRITIS THROUGH DEVELOPMENT OF PRACTICAL AND EDUCATIONAL TOOLS. (June 2019) - Burmester, Gerd Rüdiger; Laar, Mart van de; Alvaro-Gracia, Jose-Maria; Betteridge, Neil; Calvo, Jaime; Combe, Bernard; Durez, Patrick; Ferreira, Ricardo J.O; Fautrel, Bruno; Gabay, Cem; Iagnocco, Annamaria; Montecucco, Carlomaurizio; et al.
Abstract : Background: Despite advances in the treatment armamentarium for rheumatoid arthritis (RA) over the last decade, several unmet needs remain within RA management. Objectives: To enhance scientific knowledge and improve patient care by providing practical tools and evidence-based awareness – in line with EULAR recommendations – on how to implement optimal RA management and address identified needs. Methods: The eRA (evolving the management of RA) programme convened a Steering Committee (SC) of 17 European and International experts in RA, including representation from rheumatologists, nurses, health professionals and patients. Through literature search and assessment of expert opinion, 4 core areas of unmet need were identified: delays in referral and initiation of disease-modifying anti-rheumatic drugs, inconsistent application of treat-to-target strategy, sub-optimal identification and management of comorbidities, and a growing need to actively engage patients with their care. Several clinical and educational gaps associated with these unmet needs were also identified. To fill these gaps and support application of an optimal approach to RA management, practical and educational tools were developed. A cascade process engaging national leaders in rheumatology was then initiated to disseminate the tools to health professionals across Europe, with tools being updated in participating countries to ensure alignment with local practices and individual country needs. Broader programme dissemination is supported by congress activities and a digital communication plan. The eRA programme is funded by Sanofi Genzyme. Programme direction and content creation are driven by the SC. Results: A suite of 12 educational tools was developed (Figure 1 ), including educational slides to raise awareness of unmet needs, self-reflection questionnaires to evaluate personal practice alongside EULAR recommendations, case scenarios outlining the optimal approach to management, and clinical checklists to support daily practice. The process to disseminate these tools commenced in November 2017 with a Multi-Country Workshop, which convened 43 national leaders in rheumatology from countries participating in the programme. Feedback on the eRA tools at this meeting was positive, and in 2018, additional countries were onboarded to the programme. Launch of a digital web-platform aims to further support dissemination of the eRA tools. Conclusion: The content of the eRA programme has been well-received, largely due to the programme's flexible approach, which is sympathetic to individual country needs. As the cascade process continues, it is anticipated that many more health professionals and patients will benefit from the eRA tools. References: Disclosure of Interests: Gerd Rüdiger Burmester Consultant for: Roche, Sanofi-Genzyme, Speakers bureau: Roche, Sanofi-Genzyme, Mart van de Laar Grant/research support from: AbbVie, Eli Lilly, Janssen-Cilag, Merck Inc, Pfizer Inc, Sanofi Genzyme, Speakers bureau: Eli Lilly, Pfizer Inc, Jose-Maria Alvaro-Gracia Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer Inc, Roche, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer Inc, Roche, Sanofi, and UCB, Neil Betteridge Consultant for: Amgen, Eli Lilly, Grunenthal, GSK, Heart Valve Voice, Janssen, Roche, Sanofi Genzyme and Sanofi Regeneron, Speakers bureau: Amgen, Eli Lilly, Grunenthal, GSK, Heart Valve Voice, Janssen, Roche, Sanofi Genzyme and Sanofi Regeneron, Jaime Calvo Consultant for: Bristol-Myers Squibb, Janssen, Celgene, Sanofi Genzyme, Speakers bureau: Bristol-Myers Squibb, Bernard Combe Consultant for: Abbvie, Bristol-Myers Squibb, Gilead, Janssen, Eli Lilly, MSD, Novartis, Pfizer, Roche-Chugai, Sanofi, UCB, Patrick Durez Speakers bureau: Bristol-Myers Squibb, Eli Lilly, Sanofi, Celltrion, Ricardo J.O Ferreira Consultant for: Sanofi Genzyme, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant for: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, Medac, MSD, NORDIC Pharma, Novartis, Pfizer, Roche, Sanofi-Aventis, Sanofi Genzyme, SOBI, UCB, Cem Gabay Grant/research support from: Roche, Pfizer, AB2 Bio Ltd, Consultant for: Roche, Pfizer, Lilly, AbbVie, Sanofi, Regeneron, Bristol-Myers Squibb, Novartis, UCB, AB2 Bio Ltd, Debiopharm, Annamaria Iagnocco: None declared, Carlomaurizio Montecucco Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Sanofi, Genzyme, Lilly, MSD, Pfizer, UCB, Mikkel Östergaard Grant/research support from: Abbvie, Celgene, Centocor, Merck, Novartis, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Speakers bureau: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo, Orion, Pfizer, Regeneron, Roche, and UCB, Sofia Ramiro Grant/research support from: MSD, Consultant for: AbbVie, Lilly, MSD, Novartis, Pfizer, Sanofi, Speakers bureau: AbbVie, Lilly, MSD, Novartis, Pfizer, Sanofi, Andrea Rubbert-Roth Consultant for: Chugai, Eli Lilly, Roche, and Sanofi, Speakers bureau: AbbVie, Bristol-Myers Squibb, Chugai, Hexal/Novartis, Janssen, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, and Sanofi, Tanja Stamm Grant/research support from: TS has received grant support from AbbVie., Paid instructor for: TS has received speaker fees from AbbVie, Janssen, MSD, Novartis, and Roche., Zoltán Szekanecz Grant/research support from: Pfizer, UCB, Consultant for: Pfizer, Abbvie, Roche, Sanofi, Lilly, Novartis, Speakers bureau: Pfizer, Abbvie, Roche, Sanofi, Lilly, Novartis, Peter C. Taylor Grant/research support from: Celgene, Galapagos, Eli Lilly, UCB, Consultant for: AbbVie, Galapagos, Gilead, Eli Lilly, Pfizer Inc